HIV Viral Rebound Due to a Possible Drug–Drug Interaction between Elvitegravir/Cobicistat/Emtricitabine/Tenofovir Alafenamide and Calcium-Containing Products: Report of 2 Cases. (4th January 2019) - Kang-Birken, S. Lena; El-sayed, Dena; Prichard, John
Elvitegravir/cobicistat/emtricitabine/tenofovir alafenamide (E/C/F/TAF) is a potent fixed-dose, once-daily regimen for HIV-1 treatment and has rare emergence of drug resistance. We report a potential drug–drug interaction in 2 female patients both receiving treatment for HIV and cerebral toxoplasmosis: one case between E/C/F/TAF with calcium carbonate and a second case involving leucovorin as calcium salt. Both cases resulted in rise in HIV RNA levels and emergence of M184 V mutation and resistance to elvitegravir and raltegravir. To the best of our knowledge, these 2 cases are the first reports of rapid emergence of mutation from coadministration of E/C/F/TAF and calcium.